Novel Membrane Technologies for Traditional Industrial Processes - Li, Pei (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Through reading this book, you will obtain information on: (1) the main problems in air separation and natural gas treatment by membrane separation and how to solve them; (2) processes involving membranes and new membrane materials for the more economical utilization of bio-resources; (3) energy selection and membrane development for more expedient and stable harnessing of the natural osmosis phenomenon; (4) many excellent contributions about catalytic membrane bioreactors; (5) how to fine-tune the arrangement of aquaporins (i.e., proteins identified in biological cells) to achieve superior water treatment efficiency.